Penyelesaian Sengketa Harta Gono Gini Melalui Mediasi Non Litigasi Oleh Tokoh Agama (Studi Perkara di Desa Ngadisepi Kecamatan Gemawang Kabupaten Temanggung) - Munana, Nila; Ni’matul Maula, Fitria; Na’imin, Na’imin; Zumrotun, Siti (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
Disputes over joint property or gono-gini often occur in divorce and inheritance processes, causing prolonged conflict. This study focuses on the resolution of joint property disputes through non-litigation mediation facilitated by religious leaders in Ngadisepi Village, Gemawang District, Temanggung Regency. Mediation was chosen as an alternative method that is faster, more cost-effective, and more effective in reaching agreements than litigation. Religious leaders play an important role in strengthening mediation with an approach to religious values ​​believed in by the local community. This study uses a descriptive-qualitative approach with data collected through observation and documentation. The results of the study indicate that a mediation approach involving religious leaders can provide a more emotionally and financially satisfying solution for the disputing parties. In addition, mediation helps reduce tension and accelerate conflict resolution, thereby increasing the satisfaction of all parties involved.